Behavioral Biases in Islamic Retail Investing: The Moderating Role of Demographics - Satria, Rita; Nugraha, Nugraha; Disman, Disman; Purnamasari, Imas (Share: Jurnal Ekonomi dan Keuangan Islam, 2025)
Young Muslim retail investors in the Indonesian capital market often face challenges stemming from various behavioral finance biases that can negatively impact their investment decisions. This study examines the influence of behavioral finance biases—herding, overconfidence, mental accounting, loss aversion, and status quo bias—on the investment decisions of novice Muslim retail investors in Indonesia. It further explores the moderating effects of demographic factors including generation, gender, education, and income. Using a quantitative research design, data were collected from 318 respondents through a structured questionnaire, with 310 valid responses analyzed using multiple regression and moderation analysis via Hayes’ PROCESS macro in SPSS. The results indicate that all five behavioral biases negatively affect investment decisions, and demographic variables significantly moderate these effects. These findings underscore the importance of financial education and advisory services tailored to both behavioral tendencies and Islamic financial values to support informed decision-making among young Muslim investors. Despite its demographic limitations, this study contributes to a deeper understanding of behavioral finance within the Islamic finance context.======================================================================================================== ABSTRAK - Bias Perilaku dalam Investasi Ritel Syariah: Peran Moderasi Demografis. Investor ritel Muslim pemula di pasar modal Indonesia seringkali menghadapi tantangan yang disebabkan oleh berbagai bias perilaku keuangan yang dapat berdampak negatif pada keputusan investasi mereka. Penelitian ini mengkaji pengaruh bias perilaku keuangan—herding, overconfidence, mental accounting, loss aversion, dan status quo bias—terhadap keputusan investasi investor ritel Muslim pemula di Indonesia. Studi ini juga menganalisis peran moderasi faktor demografis seperti generasi, jenis kelamin, pendidikan, dan pendapatan. Dengan menggunakan pendekatan kuantitatif, data dikumpulkan dari 318 responden melalui kuesioner terstruktur, dengan 310 data valid yang dianalisis menggunakan regresi berganda dan analisis moderasi melalui PROCESS macro dari Hayes dalam SPSS. Hasil penelitian menunjukkan bahwa kelima bias perilaku berpengaruh negatif terhadap keputusan investasi, dan variabel demografis memoderasi pengaruh tersebut secara signifikan. Temuan ini menekankan pentingnya edukasi dan layanan konsultasi keuangan yang disesuaikan dengan kecenderungan perilaku dan nilai-nilai keuangan Islam untuk mendukung pengambilan keputusan yang lebih terinformasi di kalangan investor Muslim muda. Meskipun memiliki keterbatasan pada fokus demografis, penelitian ini memberikan kontribusi terhadap pemahaman yang lebih mendalam mengenai perilaku keuangan dalam konteks keuangan Islam.